Dimensional crossover and band topology evolution in ultrathin semimetallic NiTe2 films - Joseph A. Hlevyack (Nature Portfolio, 2021)
Abstract Nickel ditelluride (NiTe2), a recently discovered Type-II Dirac semimetal with topological Dirac fermions near the Fermi energy, is expected to exhibit strong thickness-mediated electronic tunability and intrinsic two-gap superconductivity in the single-layer limit. Realizing such intriguing phenomena requires the fabrication of ultrathin NiTe2 films and an understanding of the underlying physics that is still under debate. By conducting experimental band mappings of ultrathin films prepared with molecular beam epitaxy, we reveal spectroscopic evidence for the dimensionality crossover of single-crystalline ultrathin NiTe2 films as a function of film thickness. As the film thickness increases from one to five layers, the gap in the conical topological surface states closes. Comparisons of experimental to first-principles results also highlight difficulties in fabricating atomically smooth single-layer NiTe2 films. Our results not only provide further impetus for studying emergent phenomena in NiTe2 but also underscore the limitations of fabricating NiTe2 films for device applications.